Zona Pellucida sperm‐binding protein 3 receptor distribution during Gopc−/− globozoospermic spermatogenesis. Issue 4 (6th December 2021) - Bizkarguenaga, Maider; Gomez‐Santos, Laura; Madrid, Juan Francisco; Sáez, Francisco José; Alonso, Edurne
Abstract: Globozoospermia is a type of teratozoospermia characterized by round morphology of the sperm head. Gopc −/− infertile globozoospermic murine model has failures during spermiogenesis, such as the incorrect biogenesis of the acrosome, disorganized acroplaxome and manchette, round nuclei and spiral flagella. In this study, Western blot, RT‐PCR, immunohistochemistry and immunogold were done for the localization of the acrosome protein Zona Pellucida sperm‐binding protein 3 receptor (ZP3R), also called sp56, in wild type and Gopc −/− mice testis. The ZP3R protein was located in the acrosome and pseudo‐acrosome vesicles of wild type and Gopc −/− mice, respectively. Also, it is distributed through the cytoplasm of the haploid spermatids only. The incorrect spermiogenesis of Gopc −/− mice causes a deregulation in the expression of ZP3R in the globozoospermic spermatids. Our results suggest that although the lack of GOPC causes a failure during the transport of the pre‐acrosomal vesicles, the acrosome protein ZP3R is localized in the acrosome and is distributed through the cytoplasm only during spermiogenesis. Furthermore, the failure in spermiogenesis does not impair the synthesis of ZP3R and its localization in the pre‐acrosomal vesicles. Abstract : The GOPC protein is involved in the formation of the acrosome and the deletion of the gene that encodes it results in globozoospermia. In this study we have analyzed the expression of the acrosomal protein ZP3R in spermatogenesis of wild type individuals compared to sterile individuals lacking GOPC and consequently showing globozoospermia. The results show ZP3R expression only in haploid cells of the seminiferous tubule with a deregulated distribution in the sterile individual. Our results suggest that lack of GOPC causes a failure during pre‐acrosomal vesicle transport, which may deregulate all intracellular vesicle transport.